Pre-service Teachers’ Oral Presentation Anxiety in The Second Language in A Teacher Training Institute - Tajuddin, Mimi Rita @ Aishah binti; Yaacob, Aizan bin; Rahman, Faizahani Ab. (South Asian Journal of Social Sciences and Humanities, 2021)
Oral presentation skills are viewed as essential in terms of the pre-service teachers’ pre-service teachers professional development. They feel anxious in oral presentation that can be categorised as fear of negative evaluation (FNE), test anxiety (TA), communication apprehension (CA) as well as topic and content anxiety (TCA). Specifically, the study investigate oral presentation anxiety associated to the themes namely FNE, TA, CA and TCA in the English language classroom. Data for this study was obtained through written self reflection that was administered to 14 pre-service teachers in Institute of Teacher Education to investigate their oral presentation anxiety before and after the oral presentation. Findings put forward that most of the students express their feelings, attitudes and thoughts with oral presentation anxiety when they have to talk English in the classroom from different themes. The lecturers will have the awareness about the oral presentation anxiety to plan the teaching and learning in oral presentation classroom.